Release and deployment : an ITSM narrative account - McLean, Daniel (ITSM Consultant) (IT Governance Publishing, 2015)
Based on the real-life experience of the author and other ITSM practitioners, this book explains the common pitfalls of release and deployment in fictional form, with each chapter describing a difficult meeting with a different department head and featuring a set of pointers that our hero would have found beneficial. --